Efektifitas Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Untuk Pokok Bahasan Ujian Dan Cobaan Pada Mata Pelajaran Qur’an Hadits - Moh. Nasrul Amin (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2019)
This study aims to determine the effectiveness of the application of the jigsaw cooperative learning model for the subject matter of examinations and trials on the subject of the Qur'an hadith class XI IPA in Madrasah Aliyah Ma’arif Dadapan and to find out the learning outcomes of students taught with cooperative learning jigsaw type better rather than the achievement of student learning outcomes taught by conventional learning. This research is an experimental study, with a quasi experimental design design type nonequivalent control group dsign. The subjects of this study were 40 students. Sources of data in this study are primary and secondary data, in the form of qualitative and quantitative data. The instruments used were test, observation and questionnaire. Qualitative data analysis that is the achievement of student learning outcomes obtained from tests, student learning activities, learning management and students 'cooperative skills obtained from observation sheets and students' responses to the use of Jigsaw type cooperative learning models obtained from the questionnaire attractiveness of Jigsaw type cooperative learning models. while the quantitative data analysis that explains the learning outcomes of the experimental group and the control group is using a simple linear regression test at a 5% confidence level. The calculation results of this study found that the type of jigsaw cooperative learning is effective for the subject of examinations and trials on the subject of Qur'an hadith class XI Science. And based on the hypothesis test obtained that the experimental group learning outcomes are better than the control group learning achievements, as evidenced by the experimental class constant values ​​greater than the control class constant values ​​namely (a1) = 61.00> (a2) = 41.99.